The Employment of Figurative Language in a Motion Picture Artwork - Fitria, Nora; Ismail, Nyak Mutia; Zuhra, Cut Mulia (IJELR: International Journal of Education, Language, and Religion, 2023)
This study aimed at finding out the use of figurative language in an artwork, specifically movie called Toy Story 3. The method used in this study was descriptive qualitative which provided the necessary data analysis to gain the information needed from the movie. The data soure was movie entitled Toy Story 3 with xxxx minutes in length. In collecting data, the researcher used document analysis; later in daa analysis, the interactive analysis consisting of data reduction, data display, and dat verification was employed. Te result shows that there are three types of figurative language consisted in the movie: Metaphor, Simile, and Hyperbole. The metaphors were used to describe something by comparing it with other objects, Hyperbole ws employed iin order to make the language used in the film increase a child's imagination to infinity, and Simile usage enhances the sentences to spark the curiosity of the audience—merely children. Then, it was aso found that regarding the frequency, Metaphor occurs nine times and represents 60%, Hyperbole occurs five times and represents 33%, and Simile occurs one time and represents 7%. Iin conclusion, The movie Toy Story 3 used only a few figurative speeches because the target audience is children, hence simple forms of language uses are utilized.